Report from the Committee of Secrecy of the House of Lords of Ireland, appointed to take into consideration the matters of the sealed-up treasonable papers received from teh Commons, on the 23rd day of July last : (printed for John Stockdale, 1798)
Illustrated with a plan of Dublin, engraved for this report.